2016
DOI: 10.1074/jbc.m115.711895
|View full text |Cite
|
Sign up to set email alerts
|

Rhein Inhibits AlkB Repair Enzymes and Sensitizes Cells to Methylated DNA Damage

Abstract: The AlkB repair enzymes, including Escherichia coli AlkB and two human homologues, ALKBH2 and ALKBH3, are iron(II)-and 2-oxoglutarate-dependent dioxygenases that efficiently repair N 1 -methyladenine and N 3 -methylcytosine methylated DNA damages. The development of small molecule inhibitors of these enzymes has seen less success. Here we have characterized a previously discovered natural product rhein and tested its ability to inhibit AlkB repair enzymes in vitro and to sensitize cells to methyl methane sulfo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
61
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(65 citation statements)
references
References 62 publications
4
61
0
Order By: Relevance
“…Rhein, a natural product, is the first identified FTO inhibitor and competes with m6A-containing RNA for binding to the catalytic domain of FTO [97]. However, rhein is not an FTO-specific inhibitor, and it has been reported that rhein can also inhibit other ALKB family demethylases [98]. Meclofenamic acid (MA) is another FTO inhibitor and shows high selectivity in inhibiting FTO over ALKBH5 [99].…”
Section: Diagnosis and Therapeutic Potentialmentioning
confidence: 99%
“…Rhein, a natural product, is the first identified FTO inhibitor and competes with m6A-containing RNA for binding to the catalytic domain of FTO [97]. However, rhein is not an FTO-specific inhibitor, and it has been reported that rhein can also inhibit other ALKB family demethylases [98]. Meclofenamic acid (MA) is another FTO inhibitor and shows high selectivity in inhibiting FTO over ALKBH5 [99].…”
Section: Diagnosis and Therapeutic Potentialmentioning
confidence: 99%
“…It is of note that rhein and MA do not specifically inhibit FTO over other enzymes. For example, rhein also binds to 2OG-binding site of AlkB, a dioxygenase from Escherichia coli , and inhibits its activity [101] . As an anti-inflammatory drug, MA binds to the catalytic center of aldo–keto reductase 1C3 (AKR1C3) protein, which catalyzes the reduction of carbonyl groups on both steroids and prostaglandins in humans [102] .…”
Section: Alkbh5 and Fto Are Termed M 6 A Erasersmentioning
confidence: 99%
“…In a study of brain tumor samples taken from patients treated with alkylating drugs such as temozolomide (TMZ), all samples contained elevated levels of ALKBH2 mRNA over those from patients receiving radiotherapy . TMZ resistance in several glioblastoma cell lines as well as cisplatin resistance in H1299 lung cancer cells was suppressed by siRNA‐mediated knockdown of ALKBH2, and reduced ALKBH2 activity improves sensitivity to alkylating drugs . These findings have stimulated recent efforts to find inhibitors of ALKBH2 …”
Section: Figurementioning
confidence: 99%